Human Capital, Rent Seeking, and a Transition from Stagnation to Growth - Nils-Petter Lagerlöf; Thomas Tangerås (The Research Institute of Industrial Economics (IUI), 2005)
We present a growth model where agents divide time between rent seeking in the form of resource competition; and working in a human capital sector, interpreted as trade or manufacturing. Rent seeking exerts negative externalities on the productivity of human capital, generating multiple steady states. Adding shocks to the model
Keywords: D74; N10; O15; 330; Conflict; Long-Run Growth; Rent Seeking; in the form of violence in the rent seeking process; and changes in the size of the contested resource base; Humankapital; Rent-Seeking; Wirtschaftswachstum; Overlapping Generations